The Minang Restaurant Business Ethics: A Case Study in Yogyakarta, Indonesia - Rizal Mustansyir, Misnal Munir,; Rumambo Pandin, Moses Glorino (Opción)
Minang People are one of the famous adventurers and entrepreneurs in Indonesia. One of the efforts that they do is a restaurant. The characteristics of Minang restaurant management is profit sharing. This study shows that there are four characteristics of Minang restaurants, namely type A, type B, type C, and type D. Each type of restaurant represents a variety of business types. There is a relationship between Minang restaurant managers and the consumers, government staff, and suppliers. The violation of business norms committed by Minang restaurant managers is the absence of an employment contract between Minang restaurant managers.